Memoir of a Gulag actress - Petkevich, T. V. (Tamara Vladimirovna) (Northern Illinois University Press, 2010)
In an abridged translation that retains the grace and passion of the original, Klots and Ufberg present the stunning memoir of a young woman who became an actress in the Gulag. Tamara Petkevich had a relatively privileged childhood in the beautiful, impoverished Petrograd of the Soviet regime's early years, but when her father--a fervent believer in the Communist ideal--was arrested, 17-year-old Tamara was branded a "daughter of the enemy of the people." She kept up a search for her father while struggling to support her mother and two sisters, finish school, and enter university. Shortly before the Russian outbreak of World War II, Petkevich was forced to quit school and, against her better judgment, she married an exiled man whom she had met in the lines at the information bureau of the NKVD (People's Commissariat of Internal Affairs). Her mother and one sister perished in the Nazi siege of Leningrad, and Petkevich was herself arrested. With cinematic detail, Petkevich relates her attempts to defend herself against absurd charges of having a connection to the Leningrad terrorist center, counter-revolutionary propaganda, and anti-Semitism that resulted in a sentence of seven years' hard labor in the Gulag. While Petkevich became a professional actress in her own right years after her release from the Gulag, she learned her craft on the stages of the camps scattered across the northern Komi Republic. The existence of prisoner theaters and troupes of political prisoners such as the one Petkevich joined is a little-known fact of Gulag life. Petkevich's depiction not only provides a unique firsthand account of this world within a world but also testifies to the power of art to literally save lives. As Petkevich moves from one form of hardship to another she retains her desire to live and her ability to love. More than a firsthand record of atrocities committed in Stalinist Russia, Memoir of a Gulag Actress is an invaluable source of information on the daily life and culture of the Soviet Union at the time. Russian literature about the Gulag remains vastly underepresented in the United States, and Petkevich's unforgettable memoir will go a long way toward filling this gap. Supplemented with photographs from the author's personal archive, Petkevich's story will be of great interest to general readers, while providing an important resource for historians, political scientists, and students of Russian culture and history